Beyond the Present Constraints That Prevent a Wide Spread of Tissue Engineering and Regenerative Medicine Approaches - O'Donnell, Benjamen T.; Ives, Clara J.; Mohiuddin, Omair A.; Bunnell, Bruce A. (Frontiers in Bioengineering and Biotechnology, 2019)
Despite the success of tissue engineered medical products (TEMPs) in preclinical translational research, very few have had success in the clinical market place. This gap, referred to as the “valley of death”, is due to the large number of ventures that failed to attract or retain investor funding, promotion, and clinical acceptance of their products. This loss is attributed to a focus on a bench to bedside flow of ideas and technology, which does not account for the multitude of adoption, commercial, and regulatory constraints. The implementation of an alternative bedside to bench and back again approach permits investigators to focus on a specific unmet clinical need, defining crucial translation related questions early in the research process. Investigators often fail to properly identify key clinical adoption criteria due to their focus on improved patient outcomes. Other adoption criteria (such as price, time, ethical concerns, and place in the workflow) can cause a product to fail despite improved patient outcomes. By applying simplified business principles such as the build-measure-learn loop and the business model canvas to early-stage research projects, investigators can narrow in on appropriate research topics and define design constraints. Additionally, 86% of all clinical trials fail to result in Federal Drug Administration approval, resulting in significant economic burdens. A thorough understanding of the various regulatory pathways permits investigators to plan for future regulatory obstacles and potentially increase their chances of success. By utilizing a bedside to bench and back again approach, investigators can improve the odds that their research will have a meaningful clinical impact.